The Effect of Technical Competence on Employee Performance: A Systematic Literature Review - Ernita Sulistyorini; Nur Wening (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study aims to explore the influence of technical competence on employee performance. This study uses the Systematic Literature Review (SLR) approach, which refers to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. In the midst of the dynamics of the ever-evolving world of work, technical competence is one of the key factors in supporting increased productivity and work effectiveness. With reference to the PRISMA guidelines, a total of 21 articles published between 2020 and 2025 were systematically reviewed. The articles come from a variety of sectors, including government, private, and education. The results of the study show that technical competence consistently has a positive and significant effect on employee performance. Employees with adequate technical skills tend to complete tasks faster, produce quality output, and are able to adapt to technological changes. In addition, some studies show that the influence of technical competence can be amplified by other factors such as motivation, leadership, and work discipline. These findings support the importance of developing technical competencies as an integral part of human resource management strategies. This research provides theoretical contributions in strengthening competency-based management models, as well as practical implications for organizations in designing employee performance training and evaluation.